1990
DOI: 10.1002/jsfa.2740500202
|View full text |Cite
|
Sign up to set email alerts
|

Reducing gaseous losses of nitrogen from cattle slurry applied to grassland by the use of additives

Abstract: Losses of nitrogen ( N ) through ammonia (NH,) volatilisation and denitrification were determined following the application of cattle slurry to grassland in autumn or spring. Denitrification was examined on two contrasting soils. A system of small wind tunnels was used to measure N H , loss and an acetylene inhibition technique for denitrification. Between 31 and 84 % of the ammonium N (NH:-N) applied in slurry was lost through N H , volatilisation. Acidifying the slurry to pH c 5.5 prior to application reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 16 publications
(6 reference statements)
4
41
1
Order By: Relevance
“…Moreover, the dry matter content of manure significantly affects NH 3 emission [107]. Specifically, higher emission is observed at elevated dry matter levels (i.e., from cattle than pig slurry) [108]. Misselbrook et al [105] suggested that the physical nature of dry matter content (fibrous vs. colloidal) is an important factor influencing the soil infiltration potential of slurries.…”
Section: Post-treatment Of Biogas Residuementioning
confidence: 99%
“…Moreover, the dry matter content of manure significantly affects NH 3 emission [107]. Specifically, higher emission is observed at elevated dry matter levels (i.e., from cattle than pig slurry) [108]. Misselbrook et al [105] suggested that the physical nature of dry matter content (fibrous vs. colloidal) is an important factor influencing the soil infiltration potential of slurries.…”
Section: Post-treatment Of Biogas Residuementioning
confidence: 99%
“…(Frost et al,, 1990;Pain et al, 1990), 용탈 및 유실 (Ishima et al, 1974;Xie and Mackenzie, 1986) Means by the same letter within a column are not significantly different at 0.05 probability level according to DMRT. …”
Section: -----------------% (W/v) -----------------------------------mentioning
confidence: 98%
“…A significant amount of the ammoniacal N in LCM can be lost, as NH 3 by volatilization, shortly after LCM application to soils (Beauchamp et al, 1982;de Jonge et al, 2004;Pain et al, 1989;Pfluke et al, 2011aPfluke et al, , 2011bWebb et al, 2010). However, this depends on the properties of the LCM and soil, where manure is applied, and also on the rate, manner, timing of application and weather conditions and interactions among these factors (Beauchamp et al, 1982;Mannheim et al, 1995;Pain et al, 1990;Reijs et al, 2007;Rochette et al, 2006;Sorensen, 1998;Thompson et al, 1990aThompson et al, , 1990b. Soil incorporation of LCM, mainly by using injection techniques, seems to reduce NH 3 volatilization drastically and such techniques are now applicable not only to arable soils but also to grasslands, no-tillage and forest systems (Maguire et al, 2011a(Maguire et al, , 2011b.…”
Section: Introductionmentioning
confidence: 99%
“…Beauchamp (1986) found that on average the NH 4 -N was 53 % of the total N in LCM and 9 % in solid beef cattle manure. H o w e v e r , a h i g h a m o u n t o f t h i s N H 4 -N can be lost through NH 3 volatilization or immobilized after LCM addition to soil (Burger & Venterea, 2008;Pain et al, 1990;Sorensen & Jensen, 1995). The organically bound N in LCM is expected to mineralize slowly and provide less plant available N than solid cattle manure (Burger & Venterea, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation